Effect of silicon and acibenzolar-s-methyl on colored cotton plants infested or not with Aphis gossypii Glover (Hemiptera, Aphididae) - Alcantra,Eliana (2011)
Effect of silicon and acibenzolar-s-methyl on colored cotton plants infested or not with Aphis gossypii Glover (Hemiptera, Aphididae). The aphid Aphis gossypii is an insect pest that causes damage mainly at the beginning of the cotton plant development. The effect of resistance inductors silicon and acibenzolar-s-methyl (ASM) on the development of colored cotton plants were researched in the presence and absence of A. gossypii. Three colored cotton cultivars were sown in pots and individually infested with 25 apterous aphids, 13 days after the application of the inductors. Fifteen days after plant emergence, the silicon was applied at a dosage equivalent to 3 t/ha and acibenzolar-s-methyl in 0.2% solution of the product BION 500®. After 21 days of infestation the following parameters were evaluated: plant height, stem diameter, dry matter of aerial part and root, and total number of aphids replaced. It was verified that the plant height was reduced in the presence of aphids and all variables were negatively affected by the application of ASM. However, silicon did not affect plant development.